Migrant Workers in Malaysia and the Role of the International Labour Organization’s Conventions - Nafees, Seeni Mohamed M; Masum, Ahmad; Md Nor, Mohd Zakhiri; AhmeD, Kyaw Hla Win@Md Hassan; Noura, Cherifi (American Scientific Publishers, 2017)
Throughout the history migration of people to other countries in search of employment has occurred and it is by no means a new phenomenon. However, the recent movement of labour on temporary basis, first to the Middle East and later within Asia, has left migrant workers the most vulnerable as they are the least protected. The situation of workers employed abroad was addressed soon after the establishment of the International Labour Organization in 1919. As such, the objective of this paper is to focus on the issue of migrants workers while special reference is given to Malaysia. The paper strives to identify the reasons for migration and discusses various issues related to migrant workers in the light of International Labour Organization’s conventions such as the Migration for Employment Convention (Revised) of 1949 and the Migrant Workers (Supplementary Provisions) Convention of 1975. Special attention is given to workers’ problems such as difficulties in accessing to justice, seizure of migrant workers’ passports by employers and, administrative and contractual restrictions on their right to freedom of association. The methodology adopted in this paper is qualitative and exploratory using primary and secondary data. The paper concludes with some suggestions.